The Implementation of Guidance for Child Convicts at the Special Child Development Institution (LPKA): Pelaksanaan Pembinaan Terhadap Narapidana Anak Di Lembaga Pembinaan Khusus Anak (LPKA) - Fitriani, Rahma Eka (Universitas Bojonegoro, 2023)
It is very important to ensure that the rights of prisoners are adequately respected, protected and cared for in the criminal justice system. Given all the characteristics that guilty teenagers already have, this is very important in their case. In this scientific paper, it is described the implementation of fostering fostered children at the Special Child Development Institute. In terms of fostering child convicts according to Indonesian law, they have been placed in a special correctional institution (lapas) for children. Children's penitentiary (lapas) has been changed to a Special Child Development Institution (LPKA) which is a place for executing prison sentences for children until the child reaches 18 (eighteen) years of age. LPKA is required to organize education, skills training, guidance and fulfillment of other rights in accordance with laws and regulations. This study looks at how coaching is carried out in LPKA and analyzes it. The approach is normative legal research, which relies heavily on literature studies..